2020
DOI: 10.1002/mgg3.1368
|View full text |Cite
|
Sign up to set email alerts
|

POLE and POLD1 germline exonuclease domain pathogenic variants, a rare event in colorectal cancer from the Middle East

Abstract: Background Colorectal cancer (CRC) is a major contributor to morbidity and mortality related to cancer. Only ~5% of all CRCs occur as a result of pathogenic variants in well‐defined CRC predisposing genes. The frequency and effect of exonuclease domain pathogenic variants of POLE and POLD1 genes in Middle Eastern CRCs is still unknown. Methods Targeted capture sequencing and Sanger sequencing technologies were employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…The early onset of PTC suggests that POLE p.Thr457Met might have strong cause-effect on pathogenesis of PTC. Interestingly, this variant was also identified in one CRC patient previously by us ( 45 ). Our data indicate that this variant might predispose to not only PTC but also CRC.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The early onset of PTC suggests that POLE p.Thr457Met might have strong cause-effect on pathogenesis of PTC. Interestingly, this variant was also identified in one CRC patient previously by us ( 45 ). Our data indicate that this variant might predispose to not only PTC but also CRC.…”
Section: Discussionsupporting
confidence: 71%
“…Low expression of POLD1 was associated with poorer prognostic markers such as distant metastasis and stage IV tumours. We also found low expression of POLE and POLD1 to be associated with poor prognostic factors such as lymph node involvement, grade 3 tumours and stage III tumours in CRC ( 45 ). However, no significant association with disease-free survival was noted with both biomarkers.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have focused on the effect of POLE/POLD1 germline variants located in the exonuclease domain ( Elsayed et al, 2015 ; Bellido et al, 2016 ; Buchanan et al, 2018 ; Mur et al, 2020a ; Siraj et al, 2020 ), but limited efforts have been made to determine the functional impact of those variants identified in the polymerase domain. Their potential pathogenicity is usually based on rarity of these variants in the general population and loss-of-function intolerance scores.…”
Section: Discussionmentioning
confidence: 99%
“…POLE mutations in patients with colorectal cancer present distinct clinical characteristics, including younger age, a greater proportion of males than females, diagnosis at an earlier stage, as well as significant increasing tumor mutation burden (TMB). 8 , 13 However, owing to its low frequency, there were limited prospective, controlled, clinical trials designed to evaluate the efficacy of ICIs in colorectal cancer patients harboring POLE mutations. Instead of that, several retrospective researches and case studies have reported the efficacy of ICIs in colorectal patients with POLE mutations.…”
Section: Discussionmentioning
confidence: 99%